Well‐Paired‐Seq: A Size‐Exclusion and Locally Quasi‐Static Hydrodynamic Microwell Chip for Single‐Cell RNA‐Seq (Small Methods 7/2022). Issue 7 (20th July 2022) - Yin, Kun; Zhao, Meijuan; Lin, Li; Chen, Yingwen; Huang, Shanqing; Zhu, Chun; Liang, Xuan; Lin, Fanghe; Wei, Haopai; Zeng, Huimin; Zhu, Zhi; Song, Jia; et al.
Abstract : Inside Back Cover In article number 2200341, Song, Yang, and coworkers developed a high‐throughput and cost‐effective scRNA‐seq method (Well‐paired‐seq) for revealing the heterogeneity of single cells in complex systems. Based on size exclusion and quasi‐static hydrodynamic principles, Well‐paired‐seq achieves excellent efficiency of cell capture (≈91%), cell and bead pairing (≈82%), cell‐free RNA removal, and high throughput (≈105 cells).